Acute Sickle Cell Orbitopathy Masquerading as Orbital Cellulitis. Issue 1 (January 2018) - Stewart, Christopher M.; Sipkova, Zuzana; Hildebrand, Goran D.; Norris, Jonathan H.
Abstract : Sickle cell orbitopathy is a rare manifestation of a sickle cell crisis and can closely mimic orbital cellulitis, both clinically and radiologically. We present a case where a child presented with what was thought to be orbital cellulitis and was treated accordingly. Subtle radiologic features of sickle cell orbitopathy were initially overlooked, resulting in an incorrect diagnosis and a treatment delay for the patient. Correctly treated most cases resolve with no adverse affects, highlighting how important it is to consider acute sickle cell orbitopathy in the differential diagnosis of acute periorbital swelling in children with sickle disease.